A SUMO-dependent feedback loop senses and controls the biogenesis of nuclear pore subunits - Jérôme O. Rouvière (Nature Portfolio, 2018)
The nuclear pore complex is crucial for mediating nucleocytoplasmic exchanges. Here the authors use budding yeast to reveal a mechanism responsible of maintaining nucleoporin homeostasis by sensing changes in the complex integrity and further altering the metabolism of the corresponding mRNAs.